Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4103/ajns.ajns_13_17
|View full text |Cite
|
Sign up to set email alerts
|

The role of medical treatment in chronic subdural hematoma

Abstract: Surgery is the standard treatment for chronic subdural hematoma (CSDH), one of the common problems in neurosurgical practice. Although medical treatment was used by some authors and found some positive results, it is not accepted by many authors. The aim of this review is to give overall view of the medical management of CSDH. Action of various drugs in the pathophysiological cascade of formation of CSDH was depicted. The review of literature is done under three headings – the primary medical treatment of CSDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Such management includes frequent follow-up imaging, reversal and discontinuation of anticoagulation, and often the administration of corticosteroids (10,(26)(27)(28)(29)(30)(31)(32)(33)(34). Steroids are thought to inhibit the formation of the neomembrane and neovessels by suppressing both fibrinolysis and inflammation (35). However, treatment of cSDHs with corticosteroids has yielded mixed results.…”
Section: Demographic Characteristics and Treatmentmentioning
confidence: 99%
“…Such management includes frequent follow-up imaging, reversal and discontinuation of anticoagulation, and often the administration of corticosteroids (10,(26)(27)(28)(29)(30)(31)(32)(33)(34). Steroids are thought to inhibit the formation of the neomembrane and neovessels by suppressing both fibrinolysis and inflammation (35). However, treatment of cSDHs with corticosteroids has yielded mixed results.…”
Section: Demographic Characteristics and Treatmentmentioning
confidence: 99%
“…Most previous studies of CSDH treatment with Gorei-san have focused on its use to prevent recurrence after surgical treatment. 4 , 16 ) Few studies have considered using Gorei-san to shrink CSDH. 3 , 10 , 11 ) Furthermore, the effects of Gorei-san found in previous research are uncertain because most have been case reports or small case series with no control group.…”
Section: Discussionmentioning
confidence: 99%
“… 18 One systematic review of all conservative management methods concluded that they could be employed only in small, unorganized lesions, where the neurological status was stable. 44 …”
Section: Reevaluating the Standard Approaches To M ...mentioning
confidence: 99%